Upgrading pre-service foreign language teachers’ professional competences by means of the 4C’s educational model in XXI century (Journal of Educational Sciences, 2024)
This research is aimed at studying the process of professional and pedagogical preparation of pre-service foreign language teachers for the implementation of the 4C’s model of education in secondary school. The aim of the article is to present the results of the study of trends, directions and pedagogical conditions of effective organisation of the process of preparing students of the educational program 6В01730- “Foreign Language: two foreign languages” for the implementation of the 4C’s concept of education at school, to offer scientifically-based recommendations on the subject of professionally-oriented formation of flexible skills in future teachers. In order to study the problem, a control survey and questionnaire survey of students on the level of their knowledge and perceptions in the aspect of 4C’s concept, its implementation in school practice was conducted with the participation of 169 students of the educational program 6В01730 -“Foreign Language: two foreign languages”. The method of expert evaluation revealed the formation of pre-serviceteachers' methodological and technological skills of teaching and training schoolchildren in 4C’s skills. Educational program, educational-methodical complexes of disciplines of the training direction “Foreign language teacher”, methodical recommendations on the organisation of the educational process in order to form 4C’s competences were used as research materials.  In the course of analysing the university practice, information was obtained about the current trends, directions and gaps in the preparation of future foreign language teachers for teaching and training students in 4C’s skills. The key directions of pedagogical efforts and pedagogical conditions were identified, the integrated use of which increases the possibilities of effective design and organisation of the educational process in the university aimed at the formation of professionally- oriented 4C’s competences in students of educational program of pedagogical direction. The obtained results contribute to the development of modern models of training teachers of a new formation in higher education institutions of different countries. Also, the described approaches and models will allow university teachers, teachers' retraining and professional development courses to design and implement innovative content and methods of developing 4C’s competences in students.Key words:  4 C’s educational model, future teacher training, implementation of the 4C’s education model, pre-service foreign language teacher, 4C’s competences flexible skills, professional and pedagogical competences secondary school.